Anteseden Loyalitas Konsumen Keturunan Maluku Pada Merek Fashion M-Artwear (Value : Jurnal Manajemen dan Akuntansi, 2025)
The development of local brands is currently increasingly highlighting cultural values ​​as the main attraction in shaping consumer preferences for a brand. M-Artwear as a local brand from Maluku has succeeded in presenting a strong cultural identity through messages contained in product design. This study aims to analyze the effect of Value Congruity on Brand Loyalty through customer-brand identification and customer-brand engagement. This study uses a quantitative approach. Data were collected by distributing questionnaires to respondents who have Maluku blood, understand the brand design philosophy and have purchased the product. The data analysis technique used Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the help of SmartPLS 4.0 software. The variables studied consisted of Value Congruity, Customer Brand Identification, Customer Brand Engagement, affective brand commitment, and Brand Loyalty. The results showed that Value Congruity has a positive and significant effect on customer-brand identification and customer-brand engagement, but not directly on affective commitment or Brand Loyalty. Consumer brand identification is proven to have a significant influence on consumer brand engagement and affective commitment, while only affective commitment has a significant influence on Brand Loyalty.
Keywords: Value Congruity; Consumer Brand Identification; Consumer Brand Engagement; Affective Brand Commitment; Brand Loyalty